Heat killed Dietzia maris reduces lipopolysaccharide-induced inflammatory responses in murine adherent peritoneal cells - NOFOUZI, K.; GHAHVECHI-DIZAJI, B.; ZARRINI, G.H.; BARADARAN, B.; HAMIDIAN, G.H.; SAFARALIZADEH, R.; MCINTYRE, G.; RIPLEY, P.; MOUSAVI, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Dietzia maris (D. maris) is a gram-positive, aerobic, mycolic acid-containing actinomycete without mycelium. Actinomycetes such as Tsukamurella inchonensis reduce lipopolysaccharide- induced inflammatory responses in activated murine peritoneal macrophages. Here, the effects of D. maris on LPS-induced inflammatory responses were examined in mouse adherent peritoneal cells. D. maris was grown, harvested, and washed. Suspensions were standardized by wet weight, re-suspended in borate-buffered saline, and autoclaved. For in vivo study, each mouse was orally administered by bacterial suspension (5 × 107, 1 × 108 and 2 × 108 CFU/Mouse) consecutively for seven days. Control animals received the same amount of phosphate-buffered saline (PBS). Adherent peritoneal cells were harvested for in vitro experiments. Cells were lavaged and plated in RPMI 1640 medium, stimulated with LPS (100 ng/ml), and incubated for 2 h. Afterward, non-adherent cells were removed followed by adding freshly prepared medium. Supernatants (50 μl) were collected, centrifuged, mixed with Griess reagent, and the absorbance was measured at 560 nm. D .maris inhibited LPS-stimulated nitric oxide (NO) production in murine macrophages at concentrations of 5 × 107, 1 × 108 and 2 × 108 CFU/Mouse. Also, D. maris decreased LPS-induced production of pro-inflammatory cytokines of interleukin (IL)-6 at all doses. By contrast, tumor necrosis factor (TNF)-α was not effected by D. maris treatment of mice. Our results indicate that D. maris is a potent inhibitor of LPS-induced NO production. D. maris may be useful as a novel agent for the chemoprevention of inflammatory disease.